A survey of language learning strategies use in the English classes among form four students of Sekolah Menengah Jenis Kebangsaan Yok Bin, Melaka / Muzanoradawani Mamat @ Muhammad - Mamat @ Muhammad, Muzanoradawani (2011)
This study investigates the English Language Learning Strategy (LLS) used by form four students in secondary schools in relation to gender. In detail, it examines types and frequencies of language learning strategy frequently used by form four male and female students in English classes of secondary school by using Strategy Inventory Language Learning (SILL). Secondly, the study attempts to find out the significant differences in the use of English learning strategies between male and female in ESL classroom of form four students in the secondary school of SMJK Yok Bin. The Oxford’s (1990) Strategy Inventory for Language Learning (SILL) was administered to 150 of form four students. The aspects that were examined entail the six language learning strategies classified by Oxford (1990) as cognitive, memory, compensation, metacognitive, affective and social strategies. The independent variable was the gender and the dependent variable was the language learning strategies used by the form four students in the secondary schools. The language learning strategies were measured in terms of their ratings of the six sub-categories in the questionnaires. The data was then analyzed using the Statistical Package for The Social Science (SPSS) version 18.00. Descriptive statistics, Pearson’s Porduct Moment Correlation Coefficient and independent sample t-test were used in order to analyze the data. The findings indicated that the students of SMJK Yok Bin used a medium range of strategies. Metacognitive strategies were used most frequently whereas memory strategies were least frequently used among the students of the secondary school. The present study also found that gender did not affect the overall strategy usage of the students in the six categories of strategy and individual strategy use. Moreover, there was no significant difference between the males and females in the used of English learning strategies. This study also provides pedagogical implications and suggestions for future research.